FEATURES SAMOSTOYATELNOY WORK STUDENTOV OF MEDICAL FACULTY AT THE DEPARTMENT OF HISTOLOGY, EMBRYOLOGY TSITOL - ACHIEVEMENTS AND PROSPECTS - Шепітько, В.І.; Лисаченко, О.Д.; Єрошенко, Г.А.; Борута, Н.В. (World of Medicine and Biology, 2016)
An important element of training highly qualified doctor is a learning process, which is characterized by the interaction of pedagogical and organizational tools. An integral part of the intensification and improvement of the quality of education in favor of independent work.
Keywords: independent work; histology; cytology; embryology